Pancreatic Metastases from Ovarian Carcinoma - Diagnosis by Endsocopic Ultrasound-Guided Fine Needle Aspiration - Hasmoni, Mohamed Hadzri; Salleh, Rosemi (Malaysian Medical Associations, 2012)
Pancreatic metastases are very uncommon and originate most commonly from lung, colon, breast and kidney cancer. Ovarian adenocarcinoma has been reported as a primary site of pancreatic metastasis, but its diagnosis has rarely being reported by endoscopic ultrasound guided fine needle aspiration (EUS-FNA). We report a case of multiple metastases to the pancreas from ovarian carcinoma occurring four years after original resection of the primary tumour. Our patient presented with severe epigastric pain which was initially treated as acute pancreatitis. Further imaging modalities showed multiple large pseudocystic lesions in the pancreatic head and body. Subsequent EUSFNA confirmed that the lesions were metastatic disease from an advanced ovarian carcinoma. She underwent palliative chemotherapy and the pancreatic lesion showed receding size.